Macrophyte community structure across Serbian water-body types: foundations for developing bioassessment tools - Vukov, Dragana; Ćuk, Mirjana; Ilić, Miloš (Frontiers in Environmental Science, 2026)
Macrophytes are widely used as biological quality elements in ecological assessment, yet the extent to which they reflect water-body typology remains insufficiently evaluated in Serbia. We analyzed macrophyte assemblages from 99 sites representing nine nationally designated water-body types to determine (i) whether assemblages differ among types, (ii) which environmental gradients structure these differences, (iii) which species contribute most strongly to typological separation, and (iv) how accurately typology can be predicted from macrophyte composition. Presence-absence and abundance data were assessed using incidence-based rarefaction/extrapolation (iNEXT), non-metric multidimensional scaling (NMDS) with fitting of environmental vectors (envfit), community differentiation analysis (PERMANOVA/PERMDISP), distance-based redundancy analysis (dbRDA), Indicator Value Analysis (IndVal), dissimilarity analysis (SIMPER), and Random Forest (RF) classification. Diversity patterns, constrained ordination, and multivariate tests revealed clear typological structure, with conductivity, water temperature, and elevation emerging as the strongest predictors of community composition. IndVal, SIMPER, and RF consistently identified a small suite of submerged, floating, and emergent species that characterized individual types or shared ecological gradients. The RF classifier achieved 72.7% out-of-bag accuracy, demonstrating strong predictive signal despite heterogeneity in some modified or sparsely sampled types. Overall, macrophyte assemblages responded coherently to the interacting hydro-morphological and physicochemical gradients that define Serbia’s surface-water typology. These findings establish a robust ecological foundation for the future development of macrophyte-based bioassessment tools and support the implementation of WFD-compliant ecological status classification in Serbia.